Factors associated with basketball field goals made in the 2014 NBA finals - Vitor Ciampolini; Sérgio José Ibáñez; Eduardo Leal Goulart Nunes; Adriano Ferreti Borgatto; Juarez Vieira do Nascimento (Universidade Estadual Paulista (UNESP), 2018)
Abstract AIMS The main objective of this study was to analyze the factors that preceded field goals made in the 2014 NBA finals considering the number of passes per offense, shooting conditions, and offense type variables. METHODS We assessed field goals attempted by 27 professional players that participated in the 2014 NBA finals. Data were collected by three researchers through an adapted version of the Technical-Tactical Performance Evaluation Tool in Basketball to systematically analyze all five games of those finals. Descriptive analysis consisted in absolute and relative frequency and inferential statistics were applied through Chi-Square test, Cohen's D for effect size, and binary logistic regression test. Significance levels were set at 5% and all statistics were applied through SPSS 23.0. RESULTS Shooting efficacy was not associated with the number of passes made per offense. Regression statistics showed that shooting efficacy was highly associated with shooting condition rather than the offense type performed. However, fast breaks seem to lead to better shooting conditions (passively guarded and wide open) when compared to set and regained offenses. CONCLUSION Evidence pointed to the importance of shooting condition as a determining factor in increasing the probability of field goals made throughout the games analyzed.